Bahasa Inggris - Andriani, Diyah Iis; Nur Siswanti, Qanitah; Haryati, Haryati (Universitas Putera Batam, 2025)
EFL learners make efforts to learn speaking skills in order to communicate in the global world. Through speaking, they are able to express their feelings and thoughts. However, there are always some challenges faced by ELF learners in learning speaking, so that teachers play critical functions as they are most commonly used as prompters as well as feedback providers to motivate them to speak. The purposes of this study were to analyze the teacher’s strategies in teaching speaking to 29 students at SDIT Darul Qur'an Mulia, as well as to recognize the impacts of the strategies implemented. The writers applied qualitative research, and the case study was chosen as the design of study. To collect data, the writers conducted classroom observations to find out the teaching speaking strategies used in classroom teaching. Then, the writers conducted interview to discover the strategies’ impacts on students speaking skills by delivering questions to the teacher. As a result, there were seven types of strategies implemented to teach speaking, namely live listening, writing task, task repetition, drilling, dialogue, discussion, and conversation strategies. Further, based on the interview results, students showed positive responses to the implemented speaking strategies. Moreover, the impacts of the teacher's speaking strategies discovered include encouraging students to think positively, get more involved in learning, improve their speaking skills, and enjoy the learning process more. Therefore, the results suggest that incorporating interactive and student-centered approaches should be considered in teacher training and curriculum development to enhance students’ speaking skills.